Peran Pretreatment Deep Eutectic Solvent (Kolin Klorida– Gliserol) dalam Peningkatan Produksi Bioetanol dari Limbah Kulit Pisang melalui Fermentasi Saccharomyces cerevisiae - Irfani Ghufran Hamid; Alkanda Kurnia; Muhammad Romi (Lembaga Publikasi Ilmiah Nusantara, 2026)
Banana peel is a lignocellulosic agricultural waste with considerable potential as a feedstock for secondgeneration bioethanol production. However, the presence of lignin imparts structural recalcitrance to the biomass, limiting hydrolysis efficiency and reducing the conversion of polysaccharides into fermentable sugars. This study aimed to evaluate the effect of pretreatment duration using a choline chloride–glycerolbased Deep Eutectic Solvent (DES) on lignocellulosic composition, reducing sugar concentration, bioethanol production, and fermentation efficiency. A completely randomized design (CRD) with a single experimental factor was employed, consisting of four treatments: untreated biomass (control) and DES pretreatment for 1, 2, and 3 h, each performed in triplicate. The pretreated biomass was hydrolyzed using 2% H₂SO₄ and subsequently fermented with Saccharomyces cerevisiae for five days. Lignocellulosic composition was determined using the Chesson method, reducing sugar concentration was quantified by the dinitrosalicylic acid (DNS) assay, and bioethanol concentration was analyzed using gas chromatography. Data were subjected to one-way analysis of variance (ANOVA), followed by Tukey's post hoc test at a significance level of p < 0.05. Pretreatment duration significantly affected all measured parameters (p < 0.05). DES pretreatment for 3 h produced the lowest lignin content (10.1 ± 0.4%), the highest cellulose content (31.8 ± 0.8%), a reducing sugar concentration of 41.8 ± 1.5 g/L, a bioethanol concentration of 11.7 ± 0.4% (v/v), a bioethanol yield of 58.5 ± 2.0%, and a fermentation efficiency of 82.4%. These findings demonstrate that choline chloride–glycerol-based DES pretreatment for 3 h represents the optimum condition for enhancing the conversion of banana peel biomass into bioethanol by improving delignification, hydrolysis efficiency, and fermentation performance.